Silvia Bermúdez, La esfinge de la escritura: la poesía ética de Blanca Varela. Juan de la Cuesta, Newark, DE, 2005; 151 pp. - Conde Romero, Carlos Roberto (El Colegio de México, 2010)
Se reseña el libro:La esfinge de la escritura: la poesía ética de Blanca Varela.